2000
DOI: 10.1093/gerona/55.6.m350
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Performance Measures for the Identification of Mild to Moderate Frailty

Abstract: Background. The relative importance and association of factors contributing to physical frailty in elderly persons are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
274
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(286 citation statements)
references
References 23 publications
6
274
0
6
Order By: Relevance
“…Em apenas três estudos os critérios de representatividade da amostra não foram identificados e a forma de seleção das pessoas do estudo foi por conveniência (13)(14)(15) Todos os estudos descritos na revisão abordavam a população na faixa etária igual ou acima de 65 anos, com exceção de dois estudos no qual abordavam a faixa etária de 43 a 86 anos (5) e acima de 50 anos (12), que foram incluídos na revisão por discriminar os resultados por faixa etária, sendo assim, utilizou-se apenas os resultados da amostra com 65 anos ou mais.…”
Section: Resultsunclassified
“…Em apenas três estudos os critérios de representatividade da amostra não foram identificados e a forma de seleção das pessoas do estudo foi por conveniência (13)(14)(15) Todos os estudos descritos na revisão abordavam a população na faixa etária igual ou acima de 65 anos, com exceção de dois estudos no qual abordavam a faixa etária de 43 a 86 anos (5) e acima de 50 anos (12), que foram incluídos na revisão por discriminar os resultados por faixa etária, sendo assim, utilizou-se apenas os resultados da amostra com 65 anos ou mais.…”
Section: Resultsunclassified
“…Only 18 of 111 patients suffered a moderate to severe degree of frailty, as assessed by the PPT. (23) The wide variation in performance in this population and the relatively small number of participants per group may limit our ability to document significant differences. Results were obtained in the context of a 6-month trial, and the clinical effects of long-term WBV in this cohort remain unknown.…”
Section: Discussionmentioning
confidence: 97%
“…According to the modified PPT, 21.1% of the women were considered ''not frail'' (32-36 points), 62.4% were ''mildly frail'' (25-31 points), 15.6% were ''moderately frail'' (17-24 points), and 0.9% could no longer function independently within the community (<17 points). (23) No adverse side effects of the intervention were reported in the WBV training group, and training sessions were not experienced as a strenuous workout, resulting in a level of compliance of more than 90%. Only 5 women reported a lower compliance rate owing to personal or health problems not related to the study.…”
Section: Dropouts and Training Compliancementioning
confidence: 88%
See 1 more Smart Citation
“…This tool has been shown to be extremely predictive of frailty in the nondisabled elderly population. 18 A study conducted on elderly persons by Brown et al 19 showed that the scores obtained on the PPB test were significantly associated with measures of strength, and balance, gait, sensation, and multiple range of motion values.…”
Section: Dimensions and Models Related To Frailtymentioning
confidence: 99%